Idea of Tholos in Thracian Funerary Architecture: Chetinyova Mogila and the Shushmanets Tomb - Khozikova, Anastasia E. (Actual Problems of Theory and History of Art, 2023)
The article considers two Thracian monuments: the mounds of Chetinyova Mogila and Shushmanets. Their structure, on one hand, enables us to consider Mycenaean influences in Thracian architecture. On the other hand, the architectural design of their chambers is reminiscent of Classical Greek tholoi, such as those in Delphi and Epidaurus, and their variations — the Doric tholos in Samothrace and Arsinoion, among others. How these monuments correlate with Mycenaean and Classical tholoi in the context of Thracian funerary architecture and whether the functions and semantics of the ‘original’ tholoi were preserved, what idea could be transmitted through these forms by the Thracian customers — these are the issues this article focuses on. The analysis of the genesis of the Thracian tholos shows that the Mycenaean tradition was transmitted to Thrace indirectly through the architecture of neighboring regions, where Mycenaean influences were retained throughout the entire 1st millennium B. C. in the architectural forms (tomb types) and maintenance of the monumental burial landscape (through repeated burials in ancient mounds). The motif of the сlassical tholos-peripteros got into Thrace, most likely, in the context of the general spread of the typology and its popularity among the ruling elites not as a direct projection or system, but as an architectural imitation characteristic of the general trend of ‘eclecticism’ in the Hellenistic era. The cult of the heroized or deified ruler and the tradition of his posthumous veneration as anthropodaimon (ἀνθρωποδαίμων) characteristic for Thrace in 5th–4th centuries B. C. is closely associated with the semantics of tholoi, both classical and those going back to the Mycenaean tradition.